A framework for optimizing sustainment logistics for a US Army infantry brigade combat team. Issue 2 (12th November 2020) - Reich, Daniel; Lewis, Ira; Winkler, Austin J.; Leichty, Benjamin; Bobzin, Lauren B.
Abstract : Purpose: The purpose of this paper is to help optimize sustainment logistics for US Army brigade combat teams, which may face challenges in transporting their assigned assets. Design/methodology/approach: This paper develops a simulation framework with an integrated integer programming optimization model. The integer-programming model optimizes sustainment outcomes of supported battalions on a daily basis, whereas the simulation framework analyzes risk associated with shortfalls that may arise over the entire duration of a conflict. Findings: This work presents a scenario reflecting the steady resupply of an infantry brigade combat team during combat operations and presents an in-depth risk analysis for possible fleet compositions. Originality/value: The risk curves obtained allow decision-makers and commanders to optimize vehicle fleet design in advance of a conflict.